The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s10750-015-2575-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of benthic microhabitats in determining the effects of hydromorphological river restoration on macroinvertebrates

Abstract: Despite the large number of river restoration projects carried out worldwide, evidence for strong and long-term positive ecological effects of hydromorphological restoration on macroinvertebrates is scarce. To improve the understanding of the success and failure of restoration measures, a standardized field study was carried out in nineteen paired restored and degraded river sections in mid-sized lowland and mountain rivers throughout Europe. We investigated if there were effects of restoration on macroinverte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
74
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 50 publications
5
74
1
Order By: Relevance
“…even small patches may already have a positive effect (see . Moreover, macroinvertebrate richness depended on microhabitat diversity (see Verdonschot et al, 2015). Since restoration projects had no significant effect on microhabitat diversity (see Poppe et al, 2015), this may at least partly explain the missing effect of restoration on macroinvertebrate richness and diversity (see Verdonschot et al, 2015).…”
Section: Selected Results and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…even small patches may already have a positive effect (see . Moreover, macroinvertebrate richness depended on microhabitat diversity (see Verdonschot et al, 2015). Since restoration projects had no significant effect on microhabitat diversity (see Poppe et al, 2015), this may at least partly explain the missing effect of restoration on macroinvertebrate richness and diversity (see Verdonschot et al, 2015).…”
Section: Selected Results and Recommendationsmentioning
confidence: 99%
“…Moreover, macroinvertebrate richness depended on microhabitat diversity (see Verdonschot et al, 2015). Since restoration projects had no significant effect on microhabitat diversity (see Poppe et al, 2015), this may at least partly explain the missing effect of restoration on macroinvertebrate richness and diversity (see Verdonschot et al, 2015). These results indicate that although projects restoring river planform by widening or remeandering might increase macro-and mesoscale habitat conditions and hence are visually appealing, they often fail at increasing microhabitat diversity relevant for organism groups like macroinvertebrates.…”
Section: Selected Results and Recommendationsmentioning
confidence: 99%
“…Indeed, higher physical complexity has been related to higher biodiversity in near-natural systems, and losses of biodiversity have been documented for degraded systems with reduced physical complexity (Beisel et al 2000, Passy andBlanchet 2007). Similarly, follow-up studies of habitat restorations in streams and rivers have found that although physical complexity is frequently enhanced, this has often failed to generate the desired responses within target organism groups or ecosystem functions (Pretty et al 2003, Lepori et al 2005, Nilsson et al 2017, though examples of more successful outcomes exist (Miller et al 2010, Verdonschot et al 2016, Frainer et al 2017. Similarly, follow-up studies of habitat restorations in streams and rivers have found that although physical complexity is frequently enhanced, this has often failed to generate the desired responses within target organism groups or ecosystem functions (Pretty et al 2003, Lepori et al 2005, Nilsson et al 2017, though examples of more successful outcomes exist (Miller et al 2010, Verdonschot et al 2016, Frainer et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of invertebrates in lotic ecosystems is typically patchy, often reflecting spatial patterns which are structured around physical, chemical and trophic processes (Silva et al, 2014;Gibbins et al, 2016;Verdonschot et al, 2016). Research examining lotic environments has typically focussed on longitudinal and lateral gradients (environmental and ecological) as exemplified through the river continuum (Vannote et al, 1980;Rosi-Marshall et al, 2016) and flood pulse concepts (Junk et al, 1989;Turić et al, 2015).…”
Section: Introductionmentioning
confidence: 99%